Stability enhancement in large diameter rectangular natural circulation loops using flow restrictors. (July 2021) - Elton, D.N.; Arunachala, U.C.; Vijayan, P.K.
Abstract: Single-phase natural circulation loops (SPNCL) finds application in district heating reactors and low-power pressurized water reactors. It is not only adopted as a backup operation mode during accidental scenarios but also as the normal operating mode in several small and medium-sized advanced nuclear power plants. Stable operation is desired in such plants for smooth power generation and hence, the stability analysis of single-phase natural circulation systems assumes significance. The horizontal heater and horizontal cooler combination produce a maximum flow rate for a specific heater power but also is the most unstable compared to other configurations. Out of many instability restraining techniques, the orifice plate has been targeted by very few. The present experimental study focuses on the effect of using orifice plates (β = 0.90, 0.77, 0.64, and 0.51) on the stability of the 38.89 mm diameter rectangular loop with a horizontal heater and cooler configuration. The various operating procedures (start-up from rest, power raise from a stable steady-state, and power step down from an unstable state) have shown different stability/instability thresholds. Further, a hysteresis phenomenon was observed between the operating procedure of power raise from a stable state and the power step down from an unstable state, both exhibiting different stability thresholds. The increase in the stability threshold for β = 0.9, 0.77, and 0.64 for the operating procedure of start-up from rest was 75%, 110%, and 225% respectively compared to without orifice. Since the heater power was limited to 1100 W, the orifice of β = 0.51 was seen to be completely stable for the entire range of all three operating procedures for the same cooler conditions. From the loss coefficient (K), the effective length of the loops for β = 0.9, 0.77, 0.64, and 0.51 increased by 0.36, 1.32, 4.72, and 21.8 m respectively. Accordingly, the steady-state analytical solution with and without orifice found a good agreement with the experimental results. Thus, the present experimental investigations show that with the judicious choice of the flow restrictor, an unstable natural circulation system can be stabilized although the steady-state flow decreases.